LOW-FREQUENCY GENERATOR WITH VARIABLE FREQUENCY - Рябенький, Володимир; Худякова, Ірина (SWorldJournal, 2025)
The topic of the article is the construction of low-frequency oscillators with variable frequency based on simple RC-generators (Wien generators) of sinusoidal oscillations with resistor switches based on analog keys. The number of analog keys can be incr